2019
DOI: 10.1556/0806.47.2019.24
|View full text |Cite
|
Sign up to set email alerts
|

The QTL Mapping of the important breeding traits in winter triticale (×Triticosecale Wittm.)

Abstract: The increasing economic importance of triticale (×Triticosecale Wittm.) makes this synthetic hybrid cereal an interesting object of genetic studies. Genomic regions (QTL) of morphological winter triticale traits were determined using the mapping population of 89 doubled haploids lines (DHs) developed from F 1 hybrid of cv. 'Hewo' and cv. 'Magnat' accompanied with the genetic map consisting of 20 linkage groups assigned to the A (7), B (7), and R (6) genomes (total of 3539 DArT, SNP-DArT and SSR markers, length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
0
12
0
1
Order By: Relevance
“…For example, 4Brs411827353 on 4B appeared to represent one of the known major Rht-B1 loci(Wilhelm et al 2012). The 6Ars3762529 on chromosome 6A and NewChr5rs148736541 on chromosome 5R have been also detected previously(Alheit et al 2014;Würschum et al 2014;Wajdzik et al 2019). MTAs identi ed in hexaploid triticale not only further veri ed previous loci mapping results in wheat and rye, but also revealed new loci involved in shaping the important agronomic traits of triticale.…”
mentioning
confidence: 52%
“…For example, 4Brs411827353 on 4B appeared to represent one of the known major Rht-B1 loci(Wilhelm et al 2012). The 6Ars3762529 on chromosome 6A and NewChr5rs148736541 on chromosome 5R have been also detected previously(Alheit et al 2014;Würschum et al 2014;Wajdzik et al 2019). MTAs identi ed in hexaploid triticale not only further veri ed previous loci mapping results in wheat and rye, but also revealed new loci involved in shaping the important agronomic traits of triticale.…”
mentioning
confidence: 52%
“…Chromosome 5R was also described as a chromosome associated with rye preharvest sprouting resistance(Masojć et al 2007, Myśków et al 2010, Milczarski et al 2017. In our previous research on winter triticale genome regions associated with adult plants traits we detected nine QTL regions on chromosome 5R(Wajdzik et al 2019). Three of them, Qstl.hm.5R.1, Qph.hm.5R.1 and Qtkw.hm.5R.1 for the straw length, plant height and thousand kernel weight, respectively, were detected in similar position to all QTL regions described in this paper…”
mentioning
confidence: 91%
“…The studies on the genetic control of morphological and yieldrelated traits in cereals have been mainly focused on adult plants of wheat, barley, maize and rice (Peng et al 2011;Li et al 2015 Xin et al 2020). Contrary, for triticale not many studies have been reported so far (Wajdzik et al 2019;.…”
Section: Introductionmentioning
confidence: 99%
“…Several genetic maps have been constructed for hexaploid triticale based on diversity array technology (DArT), single-nucleotide polymorphism (SNP)-DArT, simple sequence repeats (SSR), and ampli ed fragment length polymorphism (AFLP) markers in different populations (Alheit et al 2011;Tyrka et al 2011;, 2018. These maps have been used to identify loci related to plant height (PH), spike length (SL), spikelet number per spike (SNS), grain number per spike (GNS), seed setting percentage (SSP), thousand-grain weight (TGW) and other traits in hexaploid triticale (Alheit et al 2014;Liu et al 2014Liu et al , 2016Wajdzik et al 2019;Würschum et al 2014). However, the molecular markers used in these studies were limited, and the plant materials were restricted to a few samples.…”
Section: Introductionmentioning
confidence: 99%